Comments on the draft proposal to emend the Code with respect to trace fossils - Genise, Jorge Fernando (2004)
In the recent proposal to clarify the meaning of the term ichnotaxon, Bertling et al. (2003) suggested that the Glossary definition of 'work of an animal' should be emended. To supplement the proposed definition of trace fossil, the draft included clearly worded lists of structures that qualify as trace fossils and otherwise. In the proposal, fossil cocoons, pupal cases, plant galls and spider webs are considered to be animal products instead of true trace fossils. However, a vigorous general discussion in the ichnologic community in July and August 2003 (Skolithos, 2003) resulted in a consensus that these terms include some structures that qualify as trace fossils, suggesting the need to refine the wording further. Such refinement is proposed herein to reduce ambiguity between trace and body fossils, delineating a sharper boundary around the ichnological realm.